2017
DOI: 10.1016/j.kjms.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin‐6 and pentraxin 3 as an early marker in Peyronie's disease

Abstract: Inflammation is mechanistically involved in the development of Peyronie's disease (PD). The aim of this study is to assess the relevance of serum pentraxin 3 (PTX3) and interleukin-6 (IL-6) concentrations in PD. The study enrolled 40 patients with PD in the acute phase and 40 healthy controls. Plasma PTX3 and IL-6 concentrations were evaluated in 40 patients in the acute phase of PD and 40 healthy controls by enzyme-linked immunosorbent assay. Serum concentrations of both PTX3 and IL-6 were significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Here, our data suggest that PPARγ, whose activity has been shown to be modulated by lipid ingestion (den Besten et al., 2015), could stimulate IL-6 expression through the activation of other proteins. In turn, IL-6 can induce the production of other pro-inflammatory proteins like PTX3 (Figure 6; Atar et al., 2017). Co-incidence of elevated IL-6 and lower GSH levels was previously reported (Valles et al., 2013), while obesogenic diets were shown to induce both of these effects in mice (Han et al., 2017) and rats (Govindaraj and Sorimuthu Pillai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data suggest that PPARγ, whose activity has been shown to be modulated by lipid ingestion (den Besten et al., 2015), could stimulate IL-6 expression through the activation of other proteins. In turn, IL-6 can induce the production of other pro-inflammatory proteins like PTX3 (Figure 6; Atar et al., 2017). Co-incidence of elevated IL-6 and lower GSH levels was previously reported (Valles et al., 2013), while obesogenic diets were shown to induce both of these effects in mice (Han et al., 2017) and rats (Govindaraj and Sorimuthu Pillai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from the study participants. For the power analysis, the study of Atar et al was got as reference (Atar et al., 2017 ). In that study, while the IL‐6 level was 33.8 + 29.8 ng/ml in the ED (‐) group, it was 56.9 + 26 ng/ml in the ED (+) group (Atar et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Agrawal et al 67 showed that endothelium-dependent flow-mediated dilation (FMD) is impaired in patients with PD who do not have risk factors such as atherosclerosis. Atar et al 68 showed that patients with early PD have more abundant IL-6 and pentraxin 3, and that this does not correlate with disease duration, degree of curvature, age, and level of C-reactive protein. These cytokines are released by endothelial cells, fibroblasts, monocytes as a result of traumatic events.…”
Section: Introductionmentioning
confidence: 99%